Comparison and Evaluation of Prelens Tear Film Stability by Different Noninvasive in vivo Methods - Itokawa T (Dove Medical Press, 2020)
Takashi Itokawa,1,2 Takashi Suzuki,2,3 Hiroko Iwashita,1 Yuichi Hori1,2 1Department of Ophthalmology, Toho University Graduate School of Medicine, Tokyo, Japan; 2Department of Ophthalmology, School of Medicine, Toho University, Tokyo, Japan; 3Ishizuchi Eye Clinic, Niihama, Ehime, JapanCorrespondence: Takashi SuzukiDepartment of Ophthalmology, School of Medicine, Toho University, 6-11-1, Omori-Nishi, Ota-Ku, Tokyo 143-8541, JapanTel +81-3-3762-4151Fax +81-3-3298-0030Email t-suzuki@ishizuchi-eye-clinic.jpPurpose: Prelens tear film stability of soft contact lens (SCL) play an important role for contact lens discomfort. In this study, we investigated the association between two types of noninvasive methods and evaluated the tear film stability with SCL using the methods.Patients and Methods: In experiment 1, images of ring mire were recorded with a keratograph after focusing the pigment located at the front or back of the SCL. Interferometry and videokeratoscopy were used for the assessment of tear film stability in the right eye of 10 women, with two different cosmetic daily disposable SCLs: polymacon and etafilcon A with polyvinylpyrrolidone. Time to first distortion by noninvasive keratograph break up time (NIKBUT-first) was compared to noninvasive interferometry break up time (NIBUT). In experiment 2, ten normal females wore two different daily disposable SCLs: samfilcon A and narafilcon A. NIKBUT-first and NIBUT were compared between the lenses after 8 hours of SCL wearing.Results: In experiment 1, NIBUT-first without SCL was significantly correlated to NIBUT without SCL (r=0.445, P=0.0488, Pearson’s correlation coefficients). However, NIKBUT-first with SCL was not significantly correlated with NIBUT with SCL. In experiment 2, although NIKBUT-first was not significantly different between SCLs, samfilcon A had significantly longer NIBUT than narafilcon A (P=0.0315, paired t-test).Conclusion: NIKBUT-first with SCL could be related to tear film stability between the lens and the corneal surface, but not to prelens tear film stability. NIIBUT could be a suitable method to evaluate prelens tear stability.Keywords: tear film stability, wettability, tear meniscus height, soft contact lens, silicone hydrogel lens